Emotions of University Professors and Students in Times of Pandemic: An Analysis from the Perspective of Resilience in Chilean Higher Education - Enrique Riquelme; Verónica Villarroel; Ricardo García; Carlos Pérez; Gerardo Fuentes (MDPI AG, 2023)
COVID-19 forced a change in the usual face-to-face teaching-learning process to remote modalities in a matter of weeks. An abrupt change, within the context of uncertainty surrounding the pandemic, significantly increased the stress experienced by professors, students, and their families. Black screens were also a sign of anxiety in the face of new emergency didactic interaction. It has been documented that emotions influence learning; however, few studies have analyzed learning during a pandemic from a resilience approach. The perceptions of the teaching-learning process of 654 professors and 1540 students from 34 Chilean universities were analyzed. Emotions experienced in remote education during the pandemic were studied in relation to professor empathy, respect in the virtual classroom, student/professor technological resources, didactic strategies, student participation, group work, tutoring, perception of learning, assessment, and perception of demand. The results show a direct relationship between professor and student positive emotions and the quality of perceived pedagogical practice and interaction.